DATA MINING ANALISIS HASIL PRODUKSI PT.SIMATELEX MANUFACTORY BATAM MENGGUNAKAN ALGORITMA APRIORI - Francisko Nainggolan, Francisko Nainggolan; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2023)
Data mining, also known as Knowledge Discovery in Databases, or KDD, is the process of attempting to extract valuable knowledge and information from very big databases. The A priori algorithm is one of the most often used algorithms in data mining approaches. Conversely, association rules are employed in the identification of combinations of associations between item-sets. Data mining has been used in a variety of industries, including telecommunications, education, and business or trade. Results from the application of data mining utilizing A priori algorithms, for instance, might assist businesses in making decisions regarding inventory policies. As an illustration, consider the value of an organization's inventory system and the top priorities for stocking up on to prevent product shortages. Because customers' opinions and a company's bottom line may be impacted by a shortage of inventory. As a result, a company's capacity to supply a variety of production product types is essential to ensuring that its customers receive their orders without delay and that its marketing efforts are successful. In addition to the aforementioned issues, data mining can develop a smart business environment to prepare the company for the future's fierce business competition.